PENINGKATAN KEMAMPUAN PROFESIONAL GURU MELALUI SUPERVISI AKADEMIK TEKNIK INDIVIDUAL CONFERENCE (IC) DI SDN 1 TUMPUK KECAMATAN SAWOO KABUPATEN PONOROGO - Sunowo, Sunowo (Educatio Vitae, 2016)
The class act research is entitled “The Improvement of Teacher Professional Competence through The Individual Conference Academic Supervision Technique (IC) in Tumpuk State Primary School in Sawoo, Ponorogo in Semester II 2011/2012 Academic Year.” The research is conducted towards 7 teachers in 4 cycles. Each cycle includes the steps of planning, implementation, observation, and reflection. The objectives of the research are (1) describing the role of Individual Conference Academic Supervision Technique (IC) in improving the professional competence of teachers and (2) giving the direction or guidelines to the school principals in conducting their duty as school supervisors in guiding school teachers and school staffs to be able to improve their competence and professionalism efficiently and productively. The finding of the research is there is the improvement of teacher professionalism through the application of Individual Conference Academic Supervision Technique. It is noticed by the improvement of teacher professional competence category in each cycle, in which cycle I is categorized as low and it is improving in the last cycle which is categorized as the highest. Key Words: Professional Competence, Academic Supervision, Individual Comnference Technique